Metabolic Acidosis Treatment as Part of a Strategy to Curb Inflammation - Tales Rubens de Nadai; Mariane Nunes de Nadai; Agnes Afrodite Sumarelli Albuquerque; Marco Tulio Menezes de Carvalho; Andrea Carla Celotto; Paulo Roberto Barbosa Evora (Hindawi Limited, 2013)
Abnormalities in systemic acid-base balance may induce significant changes in the immune response, and they may play a significant role in the development or maintenance of immune dysfunction. Different forms of acidosis (metabolic and respiratory) and even different types of metabolic acidosis (hyperchloremic and lactic) may produce different effects on immune function. If alkalization has, or not, some effect on inflammation control is still a matter of speculation. Studies concerning these subjects are limited justifying this paper.